Analisis Hukum Terhadap Peran Jurusita Pajak Dalam Pelaksanaan Penagihan Pajak Aktif Di Kantor Pelayanan Pajak Madya Medan - Panjaitan, Monica Christina; Muazzul, Muazzul; Barus, Utary Maharani (Universitas Medan Area, 2021)
The results of research and discussion explain the role of tax authorities in the implementation of active tax collection in the Medan Tax Office Medan to taxpayers after the first passive billing. Then in the implementation of active billing there are several stages in the implementation of billing, the issuance of warning letters, the issuance of forced mail, warrants foreclosure, and announcement of the auction. The procedure of execution of active tax collection by the tax authorities in Medan Tax Office Medan has been in accordance with the rules and applicable law. However, in terms of disbursement of tax arrears is still not optimal due to the realization of the target set has not been achieved.